Corporate culture of the higher educational institution as a basis for development of quality academic environment - Nakonechna, Nataliia; Наконечна, Наталія Василівна (Scientific Center of Innovative Researches OÜ, 2020)
The process of forming the corporate culture of the higher educational institution is a complex and long-lasting process that is changing in modern society and has to be adapted to the requirements of modern times. The basis of the corporate culture of the educational institution is the chosen mission and identification of the major basic values that form the standards of behavior of all corporation members including employees, students, clients, partners.
Keywords: academic integrity; education; corporate culture; higher educational institution